Clinical Profile, Precipitating Factors and Outcome of Hepatic Encephalopathy in Patients with Liver Cirrhosis - Bhattarai, Subash; Karki, Dipesh (Med Phoenix, 2021)
Introduction: Hepatic encephalopathy (HE) is characterized by reversible neuropsychological features and is observed with advanced and decompensated cirrhosis of the liver. Patients outcomes and survival depends on clinical presentation, identification of the precipitating factor, early management, and treatment of complications. This study aims to find out the clinical profile of cirrhotic patients with hepatic encephalopathy, their precipitating factors, and clinical outcomes in patients admitted at a tertiary care Teaching Hospital in Gandaki province, Nepal. Materials and Methods: An observational, cross-sectional, hospital-based prospective study comprising of 140 cirrhotic patients with encephalopathy was conducted over a study period of 18 months. Their clinical profile, precipitating factors, and outcomes during hospitalization including mortality were studied. The data analysis was done using SPSS version 20 and a P-value of ≤0.05 was considered significant. Results: Majority (36.5%) of the patients presented with Grade II HE. Upper gastrointestinal (GI) bleeding and spontaneous bacterial peritonitis were the most common precipitating factors. Inpatient mortality was 22.9%. The increased mortality rate was observed in patients with Child class C and with higher grading (Grade III and IV) of hepatic encephalopathy and in presence of more than two precipitating factors Conclusion: Most of the patients presented with Grade II HE. Upper gastrointestinal bleed and infections were the most common precipitating factors. Patients with Hepatic encephalopathy of Grades III and IV, those with CTP Child class C, and in presence of more than two precipitating factors have high mortality.